Features of surgical tactics in acute cholangitis depending from the mechanism of its development - Vovk, V. A. (Modern medical technology, 2019)
Purpose of the study. Improvement of acute cholangitis treatment by improving surgical tactics, depending on the mechanisms of acute cholangitis development. Materials and methods. Analysis of 135 patients with gallstone origin acute cholangitis. In 18 (13,3%) of these patients, acute cholangitis was accompanied by acute destructive cholecystitis; in 7 (5,2%) cholangitis was complicated by liver abscesses formation. Endoscopic transpapillary intervention was performed on 132 (97,8%) patients, and laparoscopic operations – 105 (7,8%). Totally, among 135 patients were 248 stages of surgical treatment. One-stage treatment for cholangitis was performed in 33 patients, 2 stage – 91 patients, and three stages – 11 patients. Results. Complications after endoscopic and laparoscopic interferences occurred in 17 (12,6%) patients. Complications after endoscopic interventions were bleeding from papilla – 4, acute pancreatitis – 3; after laparoscopic interventions – inflammatory complications of postoperative wounds – 6, conversion – 5. Died 2 (1,5%) patients, the cause of death in both cases was sepsis. Conclusion. The ascending and bladder mechanisms of acute cholangitis development with cholelithiasis require a different sequence of stages of endoscopic transpapillary and laparoscopic surgical interventions. Differentiated tactics, depending on the cause of acute cholangitis, contribute to reducing the trauma of surgical treatment and improving its results.